A prospective observational study to evaluate the association of various maternal risk factors with increasing incidence of term neonatal jaundice - George, Neetha; Dinesh, Devina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: In our setting majority of the mothers were discharged on postnatal day 3.but over the past few years the NICU admissions also increased prolonging the hospital stay of mothers leading to increase in the hospital acquired infections for both mother and baby. This study was developed in this context. Objectives: The present study was performed with the purpose of establishing the incidence of neonatal jaundice in term neonates and the role of the various maternal factors being responsible for exaggerated physiological hyperbilirubinemia in term neonates. Methods: Using the NICE gestational age-based phototherapy chart, this study analysed serum bilirubin of the term newborns on their day 2 of life. Total 155 antenatal mothers were taken for study. Associations between maternal risk factors and neonatal jaundice and comparing risk factors in early-term, term, and late-term newborns were assessed using chi-squared or Fisher’s exact testsResults: Incidence of neonatal jaundice is 58.1% in this study. Age, BMI, weight gain of the mother had no significant correlation with neonatal jaundice. Blood group incompatibility had a positive corelation (P=.001) Gestational age at the time of delivery determines the neonatal outcome. (P=.001). As gestation advances the neonatal outcomes are better. Hyperbilirubinemia incidence more at 37 -38 weeks when compared to 39 weeks. Maternal comorbidities, amniotic fluid volume changes, mode of delivery didn’t have statistical significance. when new-born factors are considered birth weight, gender growth problems, blood group has no statistical significance whereas dehydration proved to be significant (P=.001). meconium-stained amniotic fluid[P-0.034] were found to be associated with the development of neonatal jaundice.Conclusions: The prevalence of jaundice is higher in this study. maternal and foetal blood group incompatibility, gestational age at delivery, meconium-stained amniotic fluid, neonatal dehydration was found to be associated with the development of neonatal jaundice.